Penerapan Linear Programming dengan tools POM-QM dalam Analisis Biaya Purchase Order pada PT Mitsuba Indonesia, Cikande, Serang. - Alfin Naufalzain (Universitas Pamulang, 2025)
In the manufacturing industry, cost efficiency is a key factor in enhancing a company's competitiveness. PT Mitsuba Indonesia, a company engaged in the production of automotive components, faces challenges in managing the increasing costs of purchase orders. This study aims to analyze and optimize purchase order costs using the Linear Programming method, implemented through the POM-QM for Windows software. This research is based on optimization theory, particularly the Simplex method in Linear Programming, and supported by literature on quantitative decision-making in operations management. The research method used is a case study with a quantitative approach. Data collected includes demand volume, vendor capacity, unit price, and constraints related to production and logistics. The analysis was conducted by modeling the problem into an objective function to minimize total cost, while considering the existing operational constraints. Calculations were performed using POM-QM tools, which facilitated computation and result interpretation. The results show that the application of Linear Programming can significantly reduce the total purchase order cost compared to the conventional methods previously used by the company. The model also provides optimal order quantities from each vendor that satisfy the given constraints. In conclusion, the Linear Programming method supported by POM-QM is proven effective in optimizing purchase order costs. It is recommended that the company adopt this model regularly as a decision-making tool in procurement processes.